A systematic review on the effect of political imprisonment on mental health. (November 2015) - Willis, Stacey; Chou, Shihning; Hunt, Nigel C.
Abstract: Accounts of political imprisonment indicate that political prisoners are likely to be exposed to a range of traumatic events, including maltreatment, psychological, and physical torture. The objective of this review is to evaluate the effects of political imprisonment on mental health and the sequelae of symptoms after release. Eight electronic database sites were systematically searched. Four experts were contacted to obtain relevant studies. Electronic searches yielded 3544 hits and 3 publications were received from academics. Inclusion criteria were applied to references (n = 319) and included publications (n = 15) were quality assessed, using a pre-defined template, prior to data extraction and synthesis. The 15 publications included in the review contain 8 studies. Exposure to maltreatment and persecution during political imprisonment was found to differ between the countries included in the review. However, the authors of each study identified long-term mental health consequences of political imprisonment and recognized this experience as a traumatic event. Common symptoms reported by the former political prisoners included PTSD, depression and anxiety. Factors that appeared to contribute to the maintenance of PTSD included persecution after release, lack of rehabilitation, lack of employment/education opportunities, lack of social support, and isolation. Highlights: Features of political imprisonment are recognized as being traumatic. The long-term psychological consequences of political imprisonment are recognized. Political prisoners frequently report symptoms of PTSD, depression and anxiety.